Representasi Kehidupan Geisha Dalam Film Memoirs of A Geisha - Amalia, Kartika (PT. Alahyan Publisher Sukabumi, 2024)
Geisha are traditional Japanese artist-entertainers. Therefore, this research aims to represent the life of a Geisha in Memoirs of a Geisha movie, using Charles Sanders Peirce’s theory of semiotic analysis, to see the representation of the life of a Geisha in Memories of a Geisha movie. By using qualitative research that uses descriptive methods. The results of his research show that the life of a Geisha is not easy, to the point that even before becoming a Geisha someone has to undergo difficult training, Geisha must also be able to have skills such as dancing and playing musical instruments.